Emergent issues in the field of drug abuse - Levy, Judith A.; Stephens, Richard C.; McBride, Duane C. (Advances in medical sociology ;, 1999)
This is the eighth volume in a series dedicated to publishing current research and conceptual papers in the broad-ranging area of the sociology of health.